Bioelectrochemical Reactor Technology for the Treatment of Alkaline Waste Streams of Alumina Industry - Weerasinghe Mohottige, Tharanga Nimashanie (Curtin University, 2017)
The accumulation of organic impurities in particular oxalate, in the refinery process liquor is a major problem for alumina industry. These organic impurities reduce the alumina product quality and yield. The microbial oxidation of organics is a proven, environmentally friendly solution for organics destruction. This thesis demonstrates the improvements to the existing practice of aerobic organics destruction, as well as exploration of new option (i.e. BES) for organics destruction with simultaneous caustic recovery.